APPLICATION OF THE PROFILE MATCHING METHOD IN RECOMMENDING DOCTORAL CANDIDATES FOR LECTURER (CASE STUDY AT STMIK ROYAL) - Amin, Muhammad; Nurcahyo, Gunadi Widi; Yunus, Yuhandri (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2024)
Abstract: The advancement of information technology and knowledge has facilitated the production of quality information. The use of information technology has penetrated all fields, especially in the teaching domain at higher education institutions, aiding in valuable decision-making processes. This research focuses on STMIK Royal Kisaran, which faces challenges in increasing the number of doctoral-educated lecturers. To address this limitation, the study explores the implementation of a Decision Support System (DSS) using the Profile Matching method. Lecturers in higher education play a crucial role in providing education, conducting research, and contributing to society. In an effort to enhance the qualifications of lecturers, this research designs a Decision Support System using the Profile Matching method. The aim of this research is to provide recommendations for prospective lecturer candidates to pursue a Doctoral degree based on criteria factors such as length of service, functional position, research score, dedication score, age, and recognition score. Data from 46 lecturers at STMIK Royal Kisaran who meet the criteria are used to test the validity and effectiveness of the Decision Support System (DSS). Through structured analysis, it is demonstrated that the Decision Support System using the Profile Matching method successfully provides recommendations for suitable lecturer candidates to pursue doctoral studies.Keywords : decision support systems; higher education; information Technology; lecturer qualifications;  profile matching.  Abstrak: Kemajuan teknologi informasi dan ilmu pengetahuan telah menghadirkan kemudahan dalam menghasilkan informasi yang berkualitas, penggunaan teknologi informasi sudah memasuki segala bidang terutama bidang pengajaran pada perguruan tinggi dan membantu pengambilan keputusan yang bernilai. Penelitian ini berfokus pada STMIK Royal Kisaran yang mengalami kendala dalam meningkatkan jumlah dosen berpendidikan Doktor. Untuk mengatasi keterbatasan tersebut, penelitian ini mengeksplorasi penerapan Sistem Pendukung Keputusan (DSS) dengan menggunakan metode Profile Matching. Dosen pada pendidikan tinggi mempunyai peran penting dalam memberikan pendidikan, melakukan penelitian, dan memberikan kontribusi kepada masyarakat. Dalam upaya meningkatkan kualifikasi dosen, penelitian ini merancang Sistem Pendukung Keputusan dengan menggunakan metode Profile Matching. Penelitian ini bertujuan untuk memberikan rekomendasi kandidat calon dosen untuk mengejar gelar Doktor dengan berlandaskan faktor kriteria seperti lama kerja, jabatan fungsional, nilai penelitian, nilai pengabdian, umur, dan nilai rekognisi. Data dari 46 dosen STMIK Royal Kisaran yang memenuhi kriteria digunakan untuk menguji validitas dan efektivitas Sistem Pendukung Keputusan (SPK). Melalui analisis terstruktur, menunjukkan bahwa Sistem Pendukung Keputusan menggunakan metode Profile Matching berhasil memberikan rekomendasi calon dosen yang layak direkomendasikan untuk melanjutkan studi ke jenjang Doktor.Kata Kunci : kualifikasi dosen; pencocokan profil; pendidikan yang lebih tinggi; sistem pendukung keputusan; teknologi Informasi.